De, der har intet Hoved og Hierte til at læse Romaner: Serialiseringslogikker i den første danske fiktionslitteratur - Zetterberg Gjerlevsen, Simona (Passage - Tidsskrift for litteratur og kritik, 2018)
This article asks is if it is possible to identify formal qualities of serialization. It seeks the answer by going back to the first Danish attempts at writing serial fiction in the eighteenth century: Johannes Ewald’s The Foreigners (1771-1776) and Johan Clemens Tode’s The Usefulness of Love (as a serial from 1791-92; as a book in 1803). The article finds that a textual technique resembling the lyrical enjambment is useful to describe the unique suspense building that binds the episodes together in a serial. Thus, it argues that the “prose enjambment” might explain the special logic of the serial that has prevailed from the first attempts of serial fiction until today.